For another epistemological and methodological principle in education: transdisciplinarity - Aguiar, Leidiane Marques de (2023)
This article discusses the need for another epistemological and methodological principle in education: transdisciplinarity. From the prefix 'trans', transdisciplinarity emerges to overcome the disciplinary concept, and is concerned with recognizing different levels of reality from the non-classical logic of the third element, which we can understand, in the educational process, as the inclusion of the knowing student and the existence of a third possibility aside from the imposed classical duality (A and not-A). This theoretical study followed the path of Applied Linguistics (AL), was carried out during the first author's doctoral process under the second author's guidance, and aimed to understand the transdisciplinarity paradigm as other educational theoretical-methodological foundation, especially in the Academy. The work has as a theoretical contribution, fundamentally, the contemporary French philosophers Gilles Deleuze and Félix Guattari (2012a, 2003), the theoretical physicist Basarab Nicolescu (1999), the sociologist Edgar Morin (2020, 2015, 2011), and the philosopher Sílvio Gallo (2013), among other interlocutors. As a result of the research carried out, we understand the indispensability of a paradigm shift in education, intending to implement a transdisciplinary education, emancipate and consistent with the present century, capable of understanding the complexity of the current time, of integrating education and life, of reconnecting knowledge, to get involved in the methodology of uncertainty and the right to make mistakes and recognize, above all, the student - multidimensional - as the protagonist of his learning process.